Unmasking ideology in imperial and colonial archaeology : vocabulary, symbols, and legacy - Effros, Bonnie, 1965-; Lai, Guolong (Ideas, debates, and perspectives ;, 2018)
This volume addresses the entanglement between archaeology, imperialism, colonialism, capitalism, and war. Popular sentiment in the West has tended to embrace the adventure rather than ponder the legacy of archaeological explorers; allegations by imperial powers of "discovering" archaeological sites or "saving" world heritage from neglect or destruction have often provided the pretext for expanding political influence. Consequently, citizens have often fallen victim to the imperial war machine, seeing their lands confiscated, their artifacts looted, and the ancient remains in their midst commercialized. Spanning the globe with case studies from East Asia, Siberia, Australia, North and South America, Europe, and Africa, sixteen contributions written by archaeologists, art historians, and historians from four continents offer unusual breadth and depth in the assessment of various claims to patrimonial heritage, contextualized by the imperial and colonial ventures of the last two centuries and their postcolonial legacy